English gold coinage - Bull, Maurice (Spink & Son Ltd, 2020)
This brand new comprehensive guide covers every type of English gold coin and includes many new varieties, along with current prices. The arrangement is by monarch, with accompanying Bull reference numbers cross-referenced to the Standard Catalogue of British Coins. The section on Provenances lists the instances of illustrations of coins and where they have appeared, potentially proving the existence of many rare examples or those only rumoured to exist. Rarity of the coins has also been looked at in light of current evidence. English Gold Coinage is a record of the major and many minor recognised types and die-varieties of English gold coins. This indispensible guide is truly the essential handbook for any collector of English gold coinage.